ETS2 is a prostate basal cell marker and is highly expressed in prostate cancers aberrantly expressing p63. Issue 12 (15th May 2018) - Torres, Alba; Alshalalfa, Mohammed; Davicioni, Elai; Gupta, Anuj; Yegnasubramanian, Srinivasan; Wheelan, Sarah J.; Epstein, Jonathan I.; De Marzo, Angelo M.; Lotan, Tamara L.
Abstract : Background: Rare prostate carcinomas aberrantly express p63 and have an immunophenotype intermediate between basal and luminal cells. Here, we performed gene expression profiling on p63‐expressing prostatic carcinomas and compared them to usual‐type adenocarcinoma. We identify ETS2 as highly expressed in p63‐expressing prostatic carcinomas and benign prostate basal cells, with lower expression in luminal cells and primary usual‐type adenocarcinomas. Methods: A total of 8 p63‐expressing prostate carcinomas at radical prostatectomy were compared to 358 usual‐type adenocarcinomas by gene expression profiling performed on formalin fixed paraffin embedded tumor tissue using Affymetrix 1.0 ST microarrays. Correlation between differentially expressed genes and TP63 expression was performed in 5239 prostate adenocarcinomas available in the Decipher GRID. For validation, ETS2 in situ hybridization was performed on 19 p63‐expressing prostate carcinomas and 30 usual‐type adenocarcinomas arrayed on tissue microarrays (TMA). Results: By gene expression, p63‐expressing prostate carcinomas showed low cell cycle activity and low Decipher prognostic scores, but were predicted to have high Gleason grade compared to usual‐type adenocarcinomas by gene expression signatures and morphology. Among the genes over‐expressed in p63‐expressing carcinoma relative to usual‐type adenocarcinoma were known p63‐regulated genes, along with ETS2, an ETS family member previously implicated as a prostate cancer tumor suppressor gene. Across several cohorts of prostate samples, ETS2 gene expression was correlated with TP63 expression and was significantly higher in benign prostate compared to usual‐type adenocarcinoma. By in situ hybridization, ETS2 gene expression was high in benign basal cells, and low to undetectable in benign luminal cells or usual‐type adenocarcinoma. In contrast, ETS2 was highly expressed in 95% (18/19) of p63‐expressing prostate carcinomas. Conclusions: ETS2 is a predominantly basally‐expressed gene in the prostate, with low expression in usual‐type adenocarcinoma and high expression in p63‐expressing carcinomas. Given this pattern, the significance of ETS2 loss by deletion or mutation in usual‐type adenocarcinomas is uncertain.